Strategic pitching decisions and the role of heuristics in major league baseball - Jo, J. H.; Jin, H. J. (Psychology of Sport and Exercise, 2026)
This study examines pitch-location patterns and investigates how these patterns may reflect simplified evaluative cues employed by Major League Baseball batteries—pitchers and catchers. We analyze pitch-level data from the 2002-2024 seasons to examine the relative effects of traditional batting statistics, such as home runs and runs batted in, and advanced metrics, such as weighted runs created plus and wins above replacement (WAR), on out-of-zone pitch rates. The results show that traditional statistics, particularly home runs, exert a stronger influence on pitch location, consistent with the availability and representativeness heuristics. Several advanced measures, such as WAR and batting runs, also significantly affect pitch decisions, indicating that they contribute to the battery's evaluative framework. Rather than a strict divide, the evidence points to a relative weighting: under time pressure and cognitive load, traditional statistics are more cognitively accessible and therefore more influential in shaping tactical choices. These findings suggest a potential behavioral-analytical gap between organizational analytics and on-field decision-making, pointing to possible implications for coaching, scouting, and performance management.